Investment Contracts in The Context of Foreign Direct Investment as One of The Solutions to Achieve The Development of a New National Capital City - Ramadhan, Alfin (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The development of the new National Capital City is an ambitious project designed to create a modern and sustainable government center aimed at promoting equitable development and economic growth in Indonesia. In this context, the background of the study lies in the challenges faced, particularly the significant financial resources required to realize the development. One identified solution is the enhancement of Foreign Direct Investment (FDI), which can contribute to supporting infrastructure development, technology transfer, and job creation.Purposes of the Research: This study aims to analyze the role of FDI in supporting the development of the new National Capital City as a sustainable financing strategy.Methods of the Research: The method used in this research is a descriptive-qualitative approach, analyzing secondary data such as reports, government policies, and related literature to understand FDI’s contribution to national development, particularly in the context of the new National Capital City.Results Main Findings of the Research: The results indicate that FDI has great potential to accelerate new National Capital City development through the provision of foreign capital, technology capacity enhancement, and strengthening of international economic relations. However, the study also identifies challenges, such as the need for attractive investment policies and economic-political stability, to sustainably attract foreign investors. In conclusion, optimizing FDI requires synergy between government policies and adequate infrastructure support to ensure the successful realization of the new National Capital City development plan.